PENGARUH PSIKOEDUKASI TERHADAP SELF EFFICACY DAN MOTIVASI MENJALANI PENGOBATAN PADA PASIEN KANKER PAYUDARA - Bela Purnama Dewi; Diana H.Soebyakto; Noer Fadila; Riko Sandra Putra (LPPM STIKes Mitra Adiguna, 2026)
Breast cancer is a chronic disease that requires long-term treatment and often imposes substantial psychological challenges on patients. Self-efficacy and motivation are essential factors influencing patients' adherence to treatment and overall health outcomes. Low levels of self-efficacy and motivation may reduce treatment compliance and hinder recovery. Psychoeducation is a psychosocial intervention designed to improve patients' knowledge, coping skills, and confidence in managing their illness. This study aimed to examine the effect of psychoeducation on self-efficacy and treatment motivation among patients with breast cancer at Pusri Hospital, Palembang. A pre-experimental study with a one-group pretest-posttest design was conducted involving 70 breast cancer patients selected through purposive sampling. Self-efficacy was assessed using the General Self-Efficacy Scale (GSE), while motivation was measured using the Intrinsic Motivation Inventory (IMI). Before the intervention, most participants demonstrated low self-efficacy (65.7%) and low motivation (65.7%). Following psychoeducation, the proportion of participants with high self-efficacy increased to 82.9%, while 80.0% achieved high motivation. The Wilcoxon test revealed significant improvements in self-efficacy (Z = ?3.464, p = 0.001) and motivation (Z = ?3.317, p = 0.001). These findings indicate that psychoeducation is an effective non-pharmacological nursing intervention for enhancing self-efficacy and motivation among patients with breast cancer during treatment.